FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIABETES MELITUS DI RSUD SUBANG TAHUN 2025 - Eti Rohayati, (Jurnal Cakrawala Ilmiah, 2025)
: Introduction: Diabetes mellitus is a disease caused by disorders related to insulin hormone deficiency due to the pancreas' inability to produce it or the body's cells being unable to effectively utilize the insulin produced. Objective: To determine the factors associated with the incidence of diabetes mellitus at Subang Regional General Hospital in 2025. The subjects of this study were 90 patients with diabetes mellitus at Subang Hospital in 2025. Method: This research employed a quantitative correlational study with a cross-sectional design using accidental sampling. The study was conducted in June 2025, and the data were analyzed using the Chi-Square test. Results and Conclusion: The results showed a significant relationship between age and the incidence of diabetes mellitus (p = 0.000 < α = 0.05), a significant relationship between heredity and the incidence of diabetes mellitus (p = 0.000 < α = 0.05), a significant relationship between dietary patterns and the incidence of diabetes mellitus (p = 0.000 < α = 0.05), and a significant relationship between physical activity and the incidence of diabetes mellitus (p = 0.000 < α = 0.05). It is expected that the community will continue to collaborate more closely with healthcare workers in preventing this disease by adopting a healthy lifestyle.